From diagnostics to learning success : proceedings in vocational education and training - Beck, Klaus [Herausgeber]; Zlatkin-Troitschanskaia, Olga [Herausgeber] (Sense Publishers, 2013)
"Accelerated substantial progress regarding many fields of production and services imposes pressure upon the labor market. Employers are desperately looking for skilled workers in nearly all technological fields. All over the world this pressure reaches the national systems of vocational education and training. Along with the output orientation turn new standards are imposed, forcing firms and schools to make every endeavor to improve and remodel their programs as well as their practices to reach more and more ambitious goals. To be successful they need the results of scientific research from which they demand reliable information on methods to diagnose the state and learning progress of students and on means to foster and promote competencies of heterogeneous groups of leaners. The book offers 22 state-of-the-art articles covering the central fields of vocational education and training and reporting on new and adequate ways to deal with these challenges." (Publisher, BIBB-Doku)

Mit Beiträgen u. a. von DEISSINGER, TENBERG, METZGER, WUTTKE, SEIFRIED, SEMBILL, MINNAMEIER, KREMER, RIEDL, SCHELTEN, SEEBER und van BUER. (BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 2.2 Lerntheorien; G 1.2.3.1 Potenziale; L 4.1 Medien; I 2.2.1 Westeuropa; Berufsbildungsforschung; Lerntheorie; Schlüsselqualifikation; Mediendidaktik; Social Media; Kompetenzdiagnostik; Kompetenzentwicklung; Lehrerbildung; Deutscher Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; USA; Schweiz; Bundesrepublik Deutschland